2013
DOI: 10.2478/frp-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Polish provenances and families of pedunculate oak (Quercus robur L.) to colonisation by Phytophthora cambivora

Abstract: Abstract. Phytophthora cambivora (Straminipila, Oomycota) causes root rot and stem canker on several deciduous tree species in Europe. However, very little is known about the variation in susceptibility to P. cambivora colonisation among provenances and families of pedunculate oak (Quercus robur L.). We studied variation in susceptibility of one French and 16 Polish provenances, representing 62 families. Samples were taken from three test plots located in the Brzesko Forest District. Oak susceptibility to P. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Similar variation was observed in response of Pinus families to Fusarium circinatum (Roux et al, ), and clones of Ulmus americana L. (American elm) to Ophiostoma ulmi (Buism) (Tchernoff, ). Jankowiak, Banach, and Balonek () reported similar response of Quercus robur L. (pedunculate oak) families to Phytophthora cambivora (Petri) Buisman. Current screening trials show that there is significant potential for selecting PD tolerant P. taeda from current southeastern U.S. planting stock.…”
Section: Discussionmentioning
confidence: 84%
“…Similar variation was observed in response of Pinus families to Fusarium circinatum (Roux et al, ), and clones of Ulmus americana L. (American elm) to Ophiostoma ulmi (Buism) (Tchernoff, ). Jankowiak, Banach, and Balonek () reported similar response of Quercus robur L. (pedunculate oak) families to Phytophthora cambivora (Petri) Buisman. Current screening trials show that there is significant potential for selecting PD tolerant P. taeda from current southeastern U.S. planting stock.…”
Section: Discussionmentioning
confidence: 84%
“…Previous research into fungal colonisation of oak stands has revealed that the greatest losses are caused by pathogens of the genus Phytophthora (Rizzo et al 2002;Oszako 2005;Oszako et al 2007;McPherson et al 2013;Scanu et al 2013). In Poland, oak trees have been colonised mainly by Phytophthora quercina, Phy tophthora cactorum, Phytophthora plurivora, Phytoph thora cambivora and Phytophthora cinnamomi which are largely responsible for root diseases (Orlikowski et al 2011;Jankowiak et al 2013;Nowakowska et al 2016). Trees become more susceptible to Phytophthora pathogens under water stress conditions (Oszako and Orlikowski 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Increased populations of geometer moths were observed in Poland in the years 2011-2013, more than ever in the north-eastern regions of the country. Organisms that damage the fine roots of deciduous trees, especially oaks, are pathogens of the genus Phytophtora and Pythium (Jankowiak et al 2013). Oak decline has also been observed in Western Poland for many decades (Oszako 2007) -recently in the year 2015.…”
Section: Dieback Of Deciduous Standsmentioning
confidence: 99%